Identification and Characterization of a Cleavage Site in the Proteolysis of Orf Virus 086 Protein - Wang, Xiaoping; Xiao, Bin; Zhang, Jiafeng; Chen, Daxiang; Li, Wei; Li, Ming; Hao, Wenbo; Luo, Shuhong (Frontiers in Microbiology, 2016)
The ORF virus (ORFV) is among the parapoxvirus genus of the poxviridae family, but little is known about the proteolytic pathways of ORFV encoding proteins. By contrast, the proteolysis mechanism of the vaccinia virus has been extensively explored. Vaccinia virus core protein P4a undergoes a proteolytic process that takes place at a conserved cleavage site Ala-Gly-X (where X is any amino acid) and participates in virus assembly. Bioinformatics analysis revealed that an ORFV encoding protein, ORFV086, has a similar structure to the Vaccinia virus P4a core protein. In this study, we focus on the kinetic analysis and proteolysis mechanism of ORFV086. We found, via kinetic analysis, that ORFV086 is a late gene that starts to express at 8 hours post infection at mRNA level and 12 to 24 hours post infection at the protein level. The ORFV086 precursor and a 21kDa fragment can be observed in mature ORFV virions. The same bands were detected at only 3 hours post infection, suggesting that both the ORFV086 precursor and the 21kDa fragment are viral structural proteins. ORFV086 was cleaved from 12 to 24 hours post infection. The cleavage took place at different sites，resulting in seven bands with differing molecular weights. Sequence alignment revealed that five putative cleavage sites were predicted at C-terminal and internal regions of ORFV086. To investigate whether those cleavage sites are involved in proteolytic processing, full length and several deletion mutant ORFV086 recombinant proteins were expressed and probed. The GGS site that produced a 21kDa cleavage fragment was confirmed by identification of N/C-terminal FLAG epitope recombinant proteins, site-directed mutagenesis and Pulse-chase analysis. Interestingly, chase results demonstrated that, at late times, ORFV086 is partially cleaved. Taken together, we concluded that GGS is a cleavage site in ORFV086 and produces a 21kDa fragment post infection. Both ORFV086 precursor and the 21kDa fragment are structural proteins of mature ORFV virions. ORFV086 and its cleaved products are indispensable for correct assembly of mature viral particles and this proteolytic processing of ORFV086 may play an essential role in viral morphogenic transition.